(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The struggle for a solvent consumer in the insurance market creates new conditions for economic activity. The subjects of the market develop new schemes and mechanisms for interaction between insurance companies and other financial organizations, and increasingly involve commercial network organizations in the sale process. In modern conditions, the process of managing sales of insurance products is inextricably linked with the construction of a marketing communications system. One of the areas of development of insurance companies is the increase in the number of channels of communication with customers, the formation of a mechanism for the interaction of these channels. For example, in the European Union, one of the key channels for selling insurance products is the sale of insurance products by banks, called bank insurance. In Europe, bank insurance received the greatest development in the sale of life insurance products and pension insurance. In recent years, in foreign insurers, one of the most promising and popular options for banking and insurance cooperation is the creation of joint projects in the area of organization of complex financial services to customers. For many reasons, including increasing competitiveness and winning a significant market share, the model of a financial supermarket is the most viable option for cooperation cooperation. At the same time, the financial supermarket is a model of the client-oriented business, it represents a single integrated channel of consumers’ access to financial services, including insurance ones. In the framework of this article, we present the results of a study of the sales channels of domestic insurance products, an assessment of the status and trends in the development of partnership programs for the interaction of insurance companies and non-insurance intermediaries. The conclusion is made about perspective directions of management of sales of insurance products.